ANALISIS PENGARUH PERMINTAAN PASAR BURUH DI QATAR TERHADAP KONTINUITAS ARUS BURUH MIGRAN KE QATAR - Cesare, Nehemia; Wahyudi, Fendy Eko (Journal of International Relations, 2018)
Qatar is a country with a massive influx of immigration. Compared to other Gulf Cooperation Council (GCC) states, Qatar has the highest ratio of immigrant in their country. Generally, immigrants migrate to Qatar to become a migrant labor. Although Qatar has received massive public scrutiny because of being the host of the 2022 FIFA World Cup, Qatar continues to generate a consistent and increasing influx of migrant. This raises a question of what actually causes the incessant and massive demand of Qatar towards migrant labors. The purpose of this study is to understand the cause of the increasing number of migrant labors that migrate to Qatar despite of Qatar’s reputation in the international stage. This study uses one of the theory of international migration, which is the dual-labor market theory. This perspective focuses the analysis on Qatar as a model of industrial country in a modern society, indicated by its unavoidable need for migrant workers. This study concludes that the demand of Qatar’s labor market plays the most significant role in the continuity of migrant labor influx to Qatar.